Larvicidal Activity of Some Aromatic Thiosemicarbazone and Metal Complexes [Ni (II), Cu (II), Co (II)] Against Aedes (Stegomyia) aegypti (Linnaeus, 1762) and Aedes albopictus (Skuse, 1894) (Diptera: Culicidae) Larvae - Fatma Bursalı; İlke Demirkaya; İlknur Babahan Bircan; Fatih Mehmet Şimşek (Türkiye Parazitoloji Dergisi, 2024)

(untitled)
Objective: A series of aromatic thiosemicarbazone-oxime [TP1 and TP2] derivatives and their Ni(II), Cu(II), and Co(II) complexes were synthesized, and their larvicidal activity was evaluated against Aedes aegypti and Aedes albopictus larvae. The efficacy of these substances to Aedes albopictus larvae has been demonstrated for the first time. Methods: Laboratory colonized Aedes aegypti and Aedes albopictus larvae were subjected to larvicidal activity tests. Larval mortality rates at 24 and 48 hours were recorded and LC50 values were calculated. The study was carried out at Aydın Adnan Menderes University in 2021. Results: For Aedes aegypti, LC50 of TP1 and its Co(II) complex were 15.41, 9.75, μg/mL whereas for TP2 and its Co(II) complex, LC50 were 21.62, 20.50 μg/mL after 24 and 48 h respectively. For Aedes albopictus, TP1 and its Co(II) complex showed an LC50 of 12.06, 8.75 μg/mL, whereas TP2 and its Co(II) complex showed an LC50 of 32.87, 25.48 μg/mL, for 24, and 48 h respectively. Conclusion: Both TP1 and TP2 compounds and their Co(II) complexes presented high efficacy against the larvae; it can be said that C=S groups in thiosemicarbazone derivatives are effective in showing activity and for this reason, studies should be continued to make these components effective.